Impact of Laser Annealing Duration on the Photodetectors of n-PSi/ZnO/Pt - Motahher A Qaeed, (International Journal of Nanoelectronics and Materials (IJNeaM), 2025)
This research was devoted to studying the effect of Nd:YAG laser pulses at different annealing times (30, 60, and 90 min) at a flux of 10 ns in air at room temperature on the performance of an n-PSi/ZnO-based metal-semiconductor-metal (MSM) UV detector. By coupling thermal and photon energy, heterojunctions of n-PSi/ZnO NCs were generated, highlighting a promising approach for developing renewable energy technologies through efficient light harvesting and conversion.In this work electro-photochemical etching were used at room temperature (27°C) to create n-type porous silicon (n-PSi) layers on Si (111) substrates. The substrates had an etched area of 1 cm² and measured 1.5 cm by 1.5 cm. The n-PSi thicknesses at various current densities (15, 30, and 45 mA/cm²) were 9.6, 28.71, and 62.92 μm, respectively. To get rid of organic, oxide, and ionic impurities, standard RCA cleaning was used. A Teflon cell with a two-electrode configuration (Si anode, Pt cathode) and an electrolyte mixture of HF, ethanol, and H₂O₂ in a 2:1:1 volume ratio were utilized in the etching process. To create MSM photodetectors, samples were etched, then patterned with a photoresist and subjected to UV light. To change the n-PSi/ZnO NCs layer, post-fabrication annealing was carried out using an Nd:YAG laser (1064 nm, 350 mJ, 10 ns pulses) with a 10 cm focus lens at different durations (30, 60, 90 min), employing photon energy matching the Si bandgap. According to the study, annealing the n-PSi/ZnO NCs layer for 60 minutes at 700°C yielded the greatest results in terms of photodetector performance, crystallinity, and morphology. The porous Si surface was covered in dense, spherical ZnO nanocrystals, as revealed by Field Emission Scanning Electron Microscope (FESEM) analysis. At longer annealing durations, the crystal size and homogeneity increased. Strong c-axis orientation and high (002) peak intensity were confirmed by XRD patterns, particularly at 60 minutes. At this annealing time, the MSM photodetector showed the best I–V linearity, the lowest leakage current, and the maximum photocurrent (119.1 μA). Additionally, rapid and consistent time-response features were noted. According to the performance table, sensitivity, responsivity (2.50 A/W), and gain peaked at 60 minutes. Annealing improved charge transfer by marginally raising the Schottky barrier height. In general, mild annealing (60 minutes) improved. Annealing improved charge transfer by marginally raising the Schottky barrier height. Overall, the electrical and optoelectronic characteristics of the device were greatly improved by moderate annealing (60 min). These results highlight how these nanostructured materials can be used in renewable energy applications, especially to enhance the performance and efficiency of optoelectronic solar energy conversion and sensing devices.